2015
DOI: 10.3390/ma8063519
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interphase in the Mechanical Behavior of Silica/Epoxy Resin Nanocomposites

Abstract: A nanoscale representative volume element has been developed to investigate the effect of interphase geometry and property on the mechanical behavior of silica/epoxy resin nanocomposites. The role of interphase–matrix bonding was also examined. Results suggested that interphase modulus and interfacial bonding conditions had significant influence on the effective stiffness of nanocomposites, while its sensitivities with respect to both the thickness and the gradient property of the interphase was minimal. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Load is transferred from epoxy to particle more efficiently for stiffer interphase, improving the overall nanocomposite performance. These results are found to be consistent with other researchers' numerical studies [16,19,31], who either employed more complicated and demanding computational methods (atomistic structures, etc) or studied the interphase of different nanocomposites (i.e. silica/epoxy), therefore extending these observations to graphene/polymer nanocomposites obtained by a more applicable finite element model.…”
Section: Modelling Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Load is transferred from epoxy to particle more efficiently for stiffer interphase, improving the overall nanocomposite performance. These results are found to be consistent with other researchers' numerical studies [16,19,31], who either employed more complicated and demanding computational methods (atomistic structures, etc) or studied the interphase of different nanocomposites (i.e. silica/epoxy), therefore extending these observations to graphene/polymer nanocomposites obtained by a more applicable finite element model.…”
Section: Modelling Resultssupporting
confidence: 89%
“…Pandele et al [15] performed molecular mechanics and dynamic simulations at atomistic scale to investigate the mechanical behaviour of the graphene-based chitosan (CS) composite with varied reinforcing content. Although Yi Hua et al [16] did not consider graphene/polymer nanocomposites, their work on the simulation of the mechanical response of silica/epoxy nanocomposite gave insight into the effect of the interphase developed between the epoxy and a nanoparticle. Finally, Spanos et al [17] described a micromechanical finite element approach for the estimation of the elastic mechanical properties of graphene-reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…Hua et al have a complete explanation on this matter. They expressed that a perfect bonding assumption can lead to an increase of the Young's modulus in the nanocomposites .…”
Section: Resultsmentioning
confidence: 99%
“…The PS/SBS blends were prepared by melt compounding via a triple‐screw extruder to achieve homogeneous mixing. The miscibility and interphase of the components are the most important factors determining its properties . In this study, the miscibility was studied by DSC, and the second heating thermograms are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%